Development and Validation of the Defending Behavior Scale of Cyberbullying for Adolescents - Hong Chen; Chuan Chen; Yunduan Li; Cuiying Fan (Behavioral Sciences, 2024)
In the context of cyberbullying, bystanders engage in a diverse array of defending behaviors, employing a range of strategies tailored to the specific forms of bullying they encounter. These defending behaviors have been demonstrated to effectively mitigate the adverse effects of cyberbullying on victims. This study involved the development of the defending behavior scale of cyberbullying for adolescents and a subsequent assessment of the scale’s reliability and validity. Firstly, the structure of defending behavior was explored based on the results of in-depth interviews and previous studies in the literature. The defending behavior scale of cyberbullying for adolescents was then developed, and 550 middle school students were selected for item analysis and exploratory factor analysis. Secondly, 526 middle school students were selected for a series of reliability and validity analyses, including tests of convergent validity, discriminant validity, and structural validity, to assess the reliability and validity of the scale. The final version of the scale comprises 24 items distributed across four dimensions: emotional support, reporting authority, aggressive defending, and problem-solving. The four factors collectively account for 66.26% of the total variance. The internal consistency coefficient α of the scale was 0.92, with the internal consistency coefficients α of the dimensions being 0.88, 0.92, 0.92, 0.92, and 0.87, respectively. The scale demonstrated good convergent validity, discriminant validity, structural validity, and criterion validity. Finally, the scale has measurement equivalence across genders. The defending behavior scale of cyberbullying for adolescents was demonstrated to possess good reliability and validity, to meet the requirements of psychometrics, and to be suitable for use in measuring defending behavior in adolescent cyberbullying.